Análisis jurídico, doctrinario y de derecho comparado sobre la sentencia 67-23- IN/24 respecto a la eutanasia - Álvarez Coronel, Amada María (2024)
In recent years, we've seen a lot of changes in society, with new beliefs, medical advancements, and different social and ideological trends sparking debates about the right to life and death. These topics have become quite controversial. The term 'dying with dignity' has become more significant lately, referring to euthanasia, which is the act of dying without pain through medical intervention. This issue isn't just medical; it also brings up ethical, moral, social, and religious questions. It covers various aspects such as the right to life, human dignity, dying with dignity, doctors serving their patients' needs, individual autonomy, freedom rights, and more. The fight to legalize euthanasia has been ongoing, aiming to allow people with incurable illnesses to die with dignity. In Ecuador, the debate on euthanasia legalization is relatively new. However, after a long struggle, euthanasia was legalized through a ruling by the Constitutional Court of Ecuador. The court found conditional constitutionality in Article 144 of the Comprehensive Organic Penal Code, which led to the legalization of euthanasia in our country. This paper explores a legal, doctrinal, and comparative law study of ruling 67-23- IN/24 concerning euthanasia. It seeks to answer the central research question: Does euthanasia violate the right to the inviolability of life? Through extensive research, we identify and analyze the arguments considered by the Constitutional Court of Ecuador regarding the impact on the right to life as a protected legal interest.